Investigating Interlingual And Intralingual Error Of Diploma III Program In Sekolah Tinggi Pariwisata Mataram : An Error Analysis Of Learners’ Use Of English As A Foreign Language - Suputra, I Gede Widya (Denpasar Institute, 2024)
Entitled Investigating Interlingual and Intralingual Error of Diploma III Program in Sekolah Tinggi Pariwisata Mataram: An Error Analysis of Learners’ Use of English as a Foreign Language, this study attempted to find out (1) the types of errors that students made in their writing, (2) the sources of those errors, (3) and why global errors were still committed by students in Diploma III Program. As such, the study was designed as a case study. It was conducted in Diploma III Program of STP Mataram and a ‘writing project’ was used to collect the data. In this research, the researcher also used questionnaire and interview to obtain additional data. The results of this study show that a total of 200 errors were made by the university students. They can be categorized into five types: The first type is omission error. The numbers of omission errors are 50 errors (25%). The second type is misinformation error. The numbers of misinformation errors are 60 errors (30%). The third type is misordering error. The numbers of misordering errors are 10 errors (5%). The fourth type is overgeneralization error. The number of overgeneralization errors is 70 errors (35%). The last type is global error. The numbers of global errors are 10 errors (5%). In relation to the language transfer causing the errors, three kinds of transfer were found, namely: interlingual transfer, intralingual transfer, and transfer of learning. In addition, in term of global errors, the researcher found two main factors that cause global errors, namely, over-literal translation and lack of information about the sentence-structure of English and English grammar